Clinical Holistic Medicine: Avoiding the Freudian Trap of Sexual Transference and Countertransference in Psychodynamic Therapy - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Sexual transference and countertransference can make therapy slow and inefficient when libidinous gratification becomes more important for both the patient and the therapist than real therapeutic progress. Sexual transference is normal when working with a patient's repressed sexuality, but the therapeutic rule of not touching often hinders the integration of sexual traumas, as this needs physical holding. So the patient is often left with sexual, Oedipal energies projected onto the therapist as an “idealized father” figure. The strong and lasting sexual desire for the therapist without any healing taking place can prolong therapy for many years, as it often does in psychodynamic psychotherapy and psychoanalysis. We call this problem “Freud's Trap”. Freud used intimate bodywork, such as massage, in the beginning of his career, but stopped, presumably for moral and political reasons. In the tradition of psychoanalysis, touch is therefore not allowed. Recent research in clinical holistic medicine (CHM), salutogenesis, and sexual healing has shown that touch and bodywork (an integral part of medicine since Hippocrates) are as important for healing as conversational therapy. CHM allows the patient to regress spontaneously to early sexual and emotional traumas, and to heal the deep wounds on body, soul, and sexual character from arrested psychosexual development. CHM treats sexuality in therapy more as the patient’s internal affair (i.e., energy work) and less as a thing going on between the patient and the therapist (i.e., transference). This accelerates healing, and reduces sexual transference and the need for mourning at the end of therapy.